UNIVERSITY OF SAN MARCOS CITY AND THE UNIVERSITY PROJECT OF THE CENTURY XX - Fabbri García, Martín (2014)
The architectural heritage of universities has played an important role during the twentieth century: the University City of Caracas, designed by architect Carlos Raúl Villanueva and University City of UNAM in Mexico are notable examples of urban planning and artistic ideals of Modern Movement in architecture. Both also have been declared World Heritage by UNESCO.In Peru the concept of contemporary heritage is a subject little studied and contemporary Peruvian architecture has few examples to refer to parent lines of urban and architectural thought in the twentieth century. The campus of the National University of San Marcos has served in the twentieth century as a catalyst for the project was discussed at University San Marcos and perfectly reflects the derivations of Peruvian republican thought. Has direct the city project promoted by the ruling classes and also testifies popular mode transformations college life references. From the 40s the introduction of modern urban and references to a Latin American context are evident in the debate around San Marcos projects. Furthermore San Marcos is one of the most important works of architecture in Peruvian currency representatives as Alfredo Dammert, Carlos Morales and others. Therefore it is interesting to study the case in point: setting stages of formation of the campus and learn about the phases of urban-typological development in the city of Lima. Submit an urban history of San Marcos campus may also contribute to greater identity of the university community with its immediate surroundings. It is necessary to build relationships of empathy that you can pipe with knowledge of evolution and the history of it.